Development of Chinese mental health first aid guidelines for assisting a person affected by a traumatic event: a Delphi expert consensus study - Yan Wang (BMC, 2021)
Abstract Background People who experience traumatic events have an increased risk of developing a range of mental disorders. Appropriate early support from people in a person’s social network may help to prevent the onset of a mental disorder or minimize its severity. Mental health first aid guidelines for assisting people who have experienced traumatic events have been developed for high-income English-speaking countries. However, they may not be appropriate for use in China due to cultural and health care system differences. The aim of this study was to develop culturally appropriate guidelines for people providing mental health first aid to people affected by traumatic events in China. Methods A Delphi expert consensus study was conducted with two panels of experts in mainland China. Experts recruited to the panels included 32 professionals with expertise in the treatment of people affected by traumatic events and 31 people with lived experience of trauma or their carers. Panel members were sent a Chinese translation of the questionnaire used for developing English-language mental health first aid guidelines. This contained 168 items describing how to help people experiencing a potentially traumatic event. Panelists were asked to rate the importance of each statement for inclusion in the Chinese guidelines. They were also encouraged to suggest any additional statements that were not included in the original questionnaire. Statements were accepted for inclusion in the adapted guidelines if they were endorsed by at least 80% of each panel as very important or important. Results Consensus was achieved after three survey rounds on 134 statements for inclusion in the adapted guidelines for China, with 127 adopted from the guidelines for English-speaking countries and 7 new items from the comments of panelists. Conclusions While many of the statements are similar to the guidelines for English-speaking countries, the panelists adapted the guidelines to China’s context, including more detailed actions on how to discuss trauma and to help the person. These guidelines will be used to form the basis of a Mental Health First Aid (MHFA) training course for China, aimed at educating the public in providing support and advice to a person who is experiencing a potentially traumatic event. Further research is needed to investigate the use of the guidelines by the Chinese public and the implementation of MHFA training in appropriate settings in China.